DESCRIPTION OF THE PUPA OF PYCNOSIPHORUS GERMAINI NUMHAUSER, 1985 (COLEOPTERA: LUCANIDAE) (Acta Entomológica Chilena, 2022)
Pupa of Pycnosiphorus germaini Numhauser, 1985 is described on material collected at Lonquimay (Malleco, Chile).
Keywords: Coleóptera, Lucanidae, Pycnosiphorus germaini, morphology, pupa, Chile